Marriage in men's lives - Nock, Steven L. (OUP E-Books., 1998)
Because men and women live in worlds that are organized around gender, their marriages reflect differing realities. This text focuses on marriage as a system of rules, customs and expectations, and shows that marriage changes men on basic dimensions of achievement, participation in public and social life, and philanthropy because marriage reinforces such behaviours as part of adult masculinity. Using a database of over 6,000 interviews with men the author has studied since 1979, the conclusions point to the nature of marriage and predict that marriage is definitely here to stay.